PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI BPR SEMERU PURWODADI - Budiwinarto, Kim; Faida, Ovia Lailatul Is (FAKULTAS EKONOMI UNWIDHA KLATEN, 2025)
This research aims to determine the influence of leaership style and work discipline on employee performance at BPR Semeru Purwodadi. BPR Semeru Purwodadi is a private banking sector. This research uses quantitative methods, data was collected through questionaires given to 58 employye BPR Semeru Purwodadi which comes from various divisions and levels. The questionaires measures the level of leaership style and work discipline in the company through the answers of each respondent, as well as assessing employee performance based on predermined indicators. The data obtained were in analysis using analytical techniques, which used were multiple regression tests, t tests, f tests, and coefficient of determination tests. The research population was 58 people with a sample of 58 respondents. The results of this research show that leadership style has a positive and not significant effect on the performance of BPR employee Semeru Purwodadi. While work discipline have a positive and significant effect on the perfomance of BPR employee Semeru Purwodadi.